2018
DOI: 10.1021/acs.jced.8b00202
|View full text |Cite
|
Sign up to set email alerts
|

Speed-of-Sound Measurements and Derived Thermodynamic Properties of Liquid Isobutane

Abstract: This article reports comprehensive and accurate measurements of the speed of sound in liquid isobutane. The measurements were carried out by a double-path-length pulse-echo technique and cover the temperature range between 200 and 420 K with pressures of up to 100 MPa. The expanded measurement uncertainties (at the 0.95 confidence level) are 2.1 mK for temperature, 0.007% for pressure, and 0.009% for the speed of sound with the exception of a few state points at low pressures and in the vicinity of the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…The temperature is measured with a long stem 25.5 Ω standard platinum resistance thermometer calibrated on the ITS-90 in the wall of the pressure vessel with an expanded uncertainty (at the 0.95 confidence level) of 2.1 mK, while the pressure is measured with two calibrated nitrogen-operated pressure balances with pressure ranges of 5 and 100 MPa, which are coupled to the sample fluid by a differential-pressure null-indicator, with an expanded uncertainty (at the 0.95 confidence level) of 85 × 10 –6 · p below 0.5 MPa, 59 × 10 –6 · p between 0.5 and 1 MPa, 39 × 10 –6 · p between 1 and 5 MPa, and 45 × 10 –6 · p above 5 MPa. The uncertainty analysis of the temperature, pressure, and speed-of-sound measurements was carried out as described in our previous works. , Table provides a summary of the uncertainty budgets for the measurements in n -pentane and isopentane at 300 K and 50.1 MPa as examples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature is measured with a long stem 25.5 Ω standard platinum resistance thermometer calibrated on the ITS-90 in the wall of the pressure vessel with an expanded uncertainty (at the 0.95 confidence level) of 2.1 mK, while the pressure is measured with two calibrated nitrogen-operated pressure balances with pressure ranges of 5 and 100 MPa, which are coupled to the sample fluid by a differential-pressure null-indicator, with an expanded uncertainty (at the 0.95 confidence level) of 85 × 10 –6 · p below 0.5 MPa, 59 × 10 –6 · p between 0.5 and 1 MPa, 39 × 10 –6 · p between 1 and 5 MPa, and 45 × 10 –6 · p above 5 MPa. The uncertainty analysis of the temperature, pressure, and speed-of-sound measurements was carried out as described in our previous works. , Table provides a summary of the uncertainty budgets for the measurements in n -pentane and isopentane at 300 K and 50.1 MPa as examples.…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainty analysis of the temperature, pressure, and speed-of-sound measurements was carried out as described in our previous works. 3,4 Table 1 provides a summary of the uncertainty budgets for the measurements in n-pentane and isopentane at 300 K and 50.1 MPa as examples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since only a few data of these seven data sets lie in the temperature range of the thermodynamic integration near or at the 1 MPa isobar and there are systematic differences between them, as will be shown in Sect. 5.1.2, the initial values for the isobaric heat capacity were derived from the density data of McLinden and Splett [5] and the speed of sound correlation for toluene by applying the procedure developed in our previous work on isobutane [2]. In this procedure, Eq.…”
Section: Toluenementioning
confidence: 99%
“…We have recently applied the method of thermodynamic integration to determine the density and isobaric and isochoric heat capacity of isobutane from an accurate speed of sound data set, which was measured with a double-path-length pulse-echo apparatus in our laboratory [2]. In that work, it was shown that initial values of the isobaric heat capacity, which are often not available, can be derived from very accurate density data sets, which cover the temperature range of the speed of sound measurements at moderate pressures.…”
Section: Introductionmentioning
confidence: 99%